Mentors’ Roles in Overseas Teaching Practicum: Professional Development and Identity Construction of Indonesian Pre-service Teachers - Rifai, Irfan; Putri, Vandanti Princessa Kharisma; Bagon-Faeldan, April M.; Nugraha, Deden Novan Setiawan (JET ADI BUANA, 2026)
This study investigates Indonesian pre-service teachers' experiences of being mentored during an overseas teaching practicum in the Philippines. Specifically, it examines the roles that mentors played in supporting pre-service teachers throughout the practicum and how such mentorship contributed to their professional development and teacher identity construction. Adopting a qualitative case study design, data were drawn from personal accounts of four Indonesian pre-service teachers who completed a one-month teaching practicum in secondary schools in the Philippines. The findings reveal three prominent mentor roles: serving as role models who exemplified professional teaching conduct and dispositions; acting as collaborators who engaged in co-planning and provided sustained guidance throughout the lesson planning process; and functioning as evaluators who delivered structured, balanced, and constructive feedback following classroom teaching sessions. Collectively, these roles underscore that mentorship extends well beyond administrative guidance, it serves as a dynamic and transformative source of professional modelling that meaningfully strengthens pre-service teachers' confidence, motivation, and emerging professional identities. These findings imply that teacher education programs should prioritize structured, cross-cultural mentorship as a strategic vehicle for fostering pre-service teachers' pedagogical competence, intercultural awareness, and long-term professional identity development.